2021
DOI: 10.54386/jam.v23i3.35
|View full text |Cite
|
Sign up to set email alerts
|

Potato late blight disease prediction using meteorological parameters in Northern Himalayas of India

Abstract: Weather parameters play an important role in the spread of potato late blight of caused by Phytophthora infestans (Mont.) de Bary has historically been serious disease of potatoes through worldwide, including India. Due to spatial variation in prevailing weather conditions, its severity varies from region to region. Disease development process and the weather parameters are well understood and have been utilized for disease developing forecasting models and decision support system. Therefore, an experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The results agree with previous studies that showed changing dynamics of the P. infestans inoculum concentration during the potato growing season [9,10,14,28,34]. However, these studies focused on the prediction of late blight risk solely based on weather factors, while assuming the constant presence of inoculum [55][56][57]. Although the infection of potato plants with P. infestans is highly dependent on weather conditions, late blight epidemics cannot be explained exclusively by weather data [7,54].…”
Section: Discussionsupporting
confidence: 89%
“…The results agree with previous studies that showed changing dynamics of the P. infestans inoculum concentration during the potato growing season [9,10,14,28,34]. However, these studies focused on the prediction of late blight risk solely based on weather factors, while assuming the constant presence of inoculum [55][56][57]. Although the infection of potato plants with P. infestans is highly dependent on weather conditions, late blight epidemics cannot be explained exclusively by weather data [7,54].…”
Section: Discussionsupporting
confidence: 89%
“…The result revealed that the soil moisture at 69 -72% of field capacity, T (min) of 25 -27ºC, T (max) of 33 -36ºC, average soil temperature of 28 -30ºC, RH (min) of 60 -72 and RH (max) of 83 -89 per cent inside the boroj are highly congenial for collar rot disease incidence (Garain et al, 2021). Dar et al, (2021) conducted and experiment in Northern Himalayas (India) for two consecutive cropping seasons (2017 and 2018) to develop a forecasting model against late blight of potato using stepwise regression analysis. T (max) and T (min) in the range of 15.0 -28.0°C and 2.0 -12.0°C were found favourable for potato blight disease.…”
Section: Multiple Regression Modelmentioning
confidence: 98%
“…Chung et al (2017) reported that increased PLRV RNA accumulation and higher numbers of PLRV-infected S. tuberosum L. plants under conditions of high temperature (30±2 °C) which was corroborated with results of this experiment as maximum temperature, bright sunshine hours and evaporation was positively correlated with PLRV incidence. Dar et al (2021) had reported that the maximum and minimum temperature, relative humidity, rainfall and wind speed appeared to be most significant factors in the potato late blight disease development. Kumar and Gupta (2016) reported that the maximum and minimum temperatures had positive correlations with whitefly population causing potato apical leaf curl virus disease while RH2 had negative correlation.…”
Section: Progressive Disease Developmentmentioning
confidence: 99%